Pengembangan Teknologi E-Marketplace Untuk Hasil Pertanian, Perkebunan Dan Perikanan Kecamatan Seranau - Fakhriza Firdaus; Lukman Bachtiar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Seranau sub-district is part of the East Kotawaringin district which covers one Urban-villages and five villages. Where most of the population is a business actor in agriculture, plantations and fisheries. However, this is not accompanied by the use of existing technology, one of which is technology in the internet sector. As we know, the benefits of the internet as an effective marketing method. With marketing that is not yet widespread, production and income are not maximized. E-Marketplace is a form of marketing using internet technology. Where as a meeting place for sellers and buyers in one site. By building an E-Marketplace, it makes it easier for business actors to market their business products.